Quantitative suitability evaluation and spatial zoning for seawater desalination water intake site selection - Huang, Pei; Sun, Yonggen; Gu, Donggi; Yan, Wenwen; Chen, Yong; Wang, Enkang (Frontiers in Environmental Science, 2022)
Seawater desalination water intake site selection has an important impact on the investment, water production cost, stable operation, and safety of seawater desalination plants. Site selection is affected by many factors, such as the natural geography, ecological environment, and social economy of coastal zones; some constraints can be directly identified as unsuitable areas for these construction projects. For the shallow water intake method of seawater desalination, this study selects suitability evaluation indicators for seawater desalination water intake site selection from the three influencing factors of basic geography, water environment, and industrial development and constructs a suitability evaluation model based on the multifactor spatial overlay analysis of the GIS platform. This model carries out a quantitative suitability evaluation of the seawater desalination water intake site selection and realizes the suitable spatial zoning for spatially selecting the water intake, thus forming a scientific, quantitative, and spatial suitability evaluation system for this process. The evaluation method was applied in the Rongcheng city offshore area of China and analyzed. The evaluation results showed that the suitable areas for seawater desalination water intake site selection comprised 304.8 square kilometers, which were mainly distributed in the offshore areas in northern Rongcheng city and near the coastline areas of its central and southern regions. The unsuitable areas covered 292.4 square kilometers, mainly distributed in the marine ecological red line areas and the coastal aquaculture areas of Rongcheng city. The evaluation results met the site selection needs of the seawater desalination water intake project in Rongcheng city. This study improves upon the existing method of seawater desalination intake site selection at the theoretical and technical levels and provides a scientific basis for the location selection and planning for water intake in large spatial ranges of coastal waters.